A bioactive hyaluronic acid–based hydrogel cross-linked by Diels–Alder reaction for promoting neurite outgrowth of PC12 cells. (July 2017) - Xing, Dongming; Ma, Lie; Gao, Changyou
In order to improve neurite outgrowth on the in situ formed hyaluronic acid–based hydrogel, furan and methacrylate groups were grafted on hyaluronic acid successively. Furthermore, a laminin-derived peptide CQAASIKVAV was covalently immobilized via the Michael addition. The furan- and peptide-modified hyaluronic acid was then cross-linked in situ by mixing with bismaleimide poly(ethylene glycol) at 37 °C to obtain a bioactive hyaluronic acid–based hydrogel. The hyaluronic acid derivatives were characterized by 1 H NMR and Fourier transform infrared spectroscopy. The gelation, swelling, and mechanical property of the hydrogels were analyzed. The modulus of the hydrogel could be tuned by changing furan substitution degree, while the peptide concentration could be changed by the ratio of furan- and peptide-modified hyaluronic acid with hyaluronic acid–furan. In vitro culture of PC12 cells showed that the longest neurite outgrowth appeared on the hyaluronic acid–poly(ethylene glycol) hydrogel with the highest peptide content (the substitution degree of peptide in furan- and peptide-modified hyaluronic acid was 23 %) and a lower threshold modulus of 4.5 kPa. The furan and methacrylate-functionalized hyaluronic acid provides a versatile platform for diverse functionalization and can be used for modulation of other cell behaviors as well.